The Influence of Internal Control, Individual Morality, Spiritual Intelligence and Suitability of Compensation on Accounting Fraud Tendencies - Astriva, Viren; Sukesti, Fatmasari; Alwiyah, Alwiyah (Economics and Business International Conference Proceeding, 2024)
The trend of accounting fraud is currently a topic that is being widely discussed. Researchers are interested in examining the influence of Internal Control, Individual Morality, Spiritual Intelligence and Suitability of Compensation on the Tendency of Accounting Fraud in Companies Operating in the Financial Institutions Sector in the Semarang City Area. This research is based on Attribution theory. This research method uses primary data sources, namely data obtained directly through questionnaires on 100 samples of workers or employees in the financial institutions sector in Semarang City. The data collection technique used for this research was a field study in the form of a questionnaire or questionnaire administered using the Accidential Sampling technique. Meanwhile, the program used in this research is SPSS 25. The research results show that Internal Control, Individual Morality and Suitability of Compensation have no effect on the Tendency of Accounting Fraud, while Spiritual Intelligence has a significant negative influence on the Tendency of Accounting Fraud.